Effect of Various Shapes of Rough Transverse Slider Bearing Equipped with Ferro-Lubricant on the Load-Tolerating Capability by Mathematical Modeling (Journal of Scientific Research, 2021)
This paper investigates the effect of various film shapes of rough transverse slider bearing with Ferro-lubricant on the bearing system's load-tolerating capability (LTC). The current article describes the efforts to improve bearing’s LTC by using a Ferro-lubricant as a non-Newtonian fluid and choosing the bearing's (piston ring’s) proper geometrical shape in the    I. C. Engine. The mathematical model and the numerical and graphical results reveal the facts about enhancing the bearing system's performance. Moreover, the adverse effect of roughness can be lessened to a certain range by growing the magnetic field's strength.